2005
DOI: 10.24266/0738-2898-23.3.138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salinity and Freezing on Acer platanoides, Tilia cordata, and Viburnum lantana

Abstract: The purpose of this study was to evaluate the effects of NaCl and freezing temperatures on dormant lateral buds of Acer platanoides L. (Norway maple), Tilia cordata Mill. (littleleaf linden), and Viburnum lantana L. (wayfaringtree viburnum). The role of bud morphology was also examined. Buds were exposed to three NaCl concentrations [0, 2000, or 16,000 mg/liter (0, 2000, 16,000 ppm)] and eleven freezing temperatures [4, −4, −8, −12, −16, −20, −24, −28, −32, −36, and −40C (39, 25, 18, 10, 3, −4, −11, −18, −26, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The adverse effects of airborne de-icers can be easily observed in evergreen trees and manifest as extensive foliage necrosis on the side of the tree facing the roadway or walkway that has received de-icing salt applications. While this form of salt stress has been less extensively examined in trees than soil salinity, studies have shown that de-icers are easily absorbed by the needles of evergreen trees and through the buds, leaf scars, and young stems of dormant deciduous trees, thereby affecting tree growth and delaying bud flushing (Dobson, 1991;Zimmerman and Jull, 2006).…”
Section: The Impact Of De-icing Salts On Streetside Soil and Vegetationmentioning
confidence: 99%
“…The adverse effects of airborne de-icers can be easily observed in evergreen trees and manifest as extensive foliage necrosis on the side of the tree facing the roadway or walkway that has received de-icing salt applications. While this form of salt stress has been less extensively examined in trees than soil salinity, studies have shown that de-icers are easily absorbed by the needles of evergreen trees and through the buds, leaf scars, and young stems of dormant deciduous trees, thereby affecting tree growth and delaying bud flushing (Dobson, 1991;Zimmerman and Jull, 2006).…”
Section: The Impact Of De-icing Salts On Streetside Soil and Vegetationmentioning
confidence: 99%
“…Urban soil conditions may also be adverse for adequate tree development. Common conditions are deficiency in nutrients (De Kimpe and Morel 2000); compaction in and around tree pits and construction sites which lowers soil aeration and water movement and impairs root growth (Smith et al 2001;Percival et al 2004); restricted water drainage and water-holding capacity; interrupted organic matter and nutrient cycling; modified soil organism activity; significant concentration levels of heavy metals (Lu et al 2003); and modified soil reactions consequential to use of de-icing salts (Zimmerman et al 2005). Indeed, during winter, large volumes of de-icing salts are applied in some cities.…”
mentioning
confidence: 99%